ChemInform Abstract: A Catalytic Borylation/Dehalogenation Route to o‐Fluoro Arylboronates. Issue 19 (May 2015) - Jayasundara, Chathurika R. K.; Unold, Jason M.; Oppenheimer, Jossian; Smith, Milton R.; Maleczka, Robert E. Jr.
Abstract: If ammonium formate is used as the hydrogen source instead of PMHS, the dehalogenation is often accompanied by deborylation.